Genetic Association and Expression of Myoglobin Gene Related to Mineral Content in IPB-D2 Chickens (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2024)
Myoglobin (MB) gene encodes the protein of myoglobin, which is a protein found in muscle tissues that plays a crucial role in binding and storing oxygen. This study aimed to analyze the polymorphism of the MB gene, examine its relationship with the meat mineral content, and analyze its expression in the liver and thigh muscle tissue of IPB-D2 chicken. A total of 55 IPB-D2 chickens were used in this study. Identification of the gene polymorphism, quantification of the mineral content, and gene expression were performed using the direct sequencing method, the Atomic Absorption Spectroscopy (AAS) method, and the qRT-PCR, respectively. Chicken thigh muscle and liver tissues were used as the source of mRNA in this study. The statistical analysis methods used were the chi-square test to test Hardy-Weinberg equilibrium, and the T-test for mineral association analysis and gene expression analysis. IPB-D2 chicken on average contains 17.81, 0.22, 16.50, and 0.34 mg/kg of Fe, Se, Zn, and Mn, respectively. Two SNPs were found in 5’UTR of the MB gene, namely SNP g.17 G>T and SNP g.25 T>C. Genotype TT (g.17 G>T) and genotype CC (g.25 T>C) were significantly (P